The efficacy and safety of once weekly injectable semaglutide (Ozempic) among patients with Type 2 diabetes in tertiary care hospital: A Retrospective Study - Misbah jabeen; Umar Yousaf Raja; Osama Istiaq; Iqra Farooq (Journal of the Pakistan Medical Association, 2026)
Objective: To assess the efficacy and safety of weekly injectable semaglutide in obese type 2 diabetes mellitus patients. Method: The retrospective, cross-sectional study was conducted at the Endocrinology Department, Shifa International Hospital, Islamabad, Pakistan, and comprised data from January 1, 2021, to January 31, 2023, of adult type 2 diabetes mellitus patients of either gender who had been prescribed weekly injectable semaglutide. Efficacy assessment was based on measuring the changes in glycated haemoglobin, bodyweight and body mass index at 3, 6, 9 and 12 months. The incidence of adverse events was also noted. Data was analysed using SPSS 26. Results: Of the 102 patients, 57(56%) were females and 45(44%) were males. Overall mean age was 50±11.17 years, and the mean diabetes duration was 8.13±6.67 years. Mean values for glycated haemoglobin, bodyweight and body mass index were significantly different at 3, 6, 9 and 12 months post-intervention compared to baseline. Nausea was reported by 26(25.5%) patients. The most common reason for stopping semaglutide was no further benefits 37(47%). Conclusion: Injectable semaglutide was found to be quite effective in managing type 2 diabetes mellitus. The treatment was well tolerated, establishing semaglutide as a valuable addition to diabetes care in Pakistan. Key Words: Semaglutide, Type 2 diabetes mellitus, Obesity.